Surface analysis of conversion coating of ASTM A 516 - Khan, Muhammed Ali; Sha, Aqueel; Yusuf, Adeel; Nisar, Salman (Cranfield University, 2022)
Surface engineering is a vital aspect of manufacturing industries owing to its benefits both in surface protection and aesthetics. It has been extensively used in various industries to guard against corrosion which is a naturally occurring and highly undesirable phenomenon. Present research has endeavored to analyze protection of ASTM A516 (Grade 70) from corrosion through surface engineering. Different methods of surface treatment and conversion coating were carried out to efficiently enhance corrosive protection. Comparative analysis of various samples was conducted to analyze their ability to resist corrosion. Samples with surface treatment followed by conversion coating were found to be effective even against 0.7% aqueous sulfuric acid with no significant cracks in the coating layer. On the other hand, conversion coated only samples showed protection against 0.35% acid. The coating of conversion coated only samples was found to have gaps/ cracks as indicated by 3% Cupric Sulfate whereas no such gaps were found in surface treated samples. Optical microscopy identified a more uniform coating thickness for surface treated samples in comparison with conversion coated only samples. In depth morphology analysis using SEM highlighted that surface treated samples had low porosity preventing the corrosion elements to reach the substrate thereby implementing higher corrosion potential.
11th International Conference on Through-life Engineering Services - TESConf 2022, 8-9 November 2022, Cranfield UK
Keywords: ASTM A 516 (Grade 70); Corrosion; Surface engineering; Conversion coating